2006
DOI: 10.1051/forest:2006033
|View full text |Cite
|
Sign up to set email alerts
|

Crown architecture and leaf habit are associated with intrinsically different light-harvesting efficiencies inQuercusseedlings from contrasting environments

Abstract: -Crown architecture and light-harvesting efficiency (Ea) were compared in seedlings of eight Quercus species from contrasting environments. Several morphological variables were measured after one year of growth under the same environmental conditions. Ea was estimated with the 3-D model Y-plant. The species were classified in four groups according to their Ea: Q. rubra-Q. alba > Q. faginea-Q. pyrenaica > Q. robur-Q. ilex-Q. coccifera > Q. suber. Principal component analysis revealed that the constraining morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Such morphological leaf traits have been interpreted as adaptations to withstand summer drought (Morrow & Mooney, ; Poole & Miller, ; Baldocchi & Xu, ; Galmés et al ., ), given that water is the main limiting resource for plant growth in Mediterranean‐type climates (Di Castri, ; Rhizopoulou & Mitrakos, ; Mediavilla & Escudero, , ; Corcuera et al ., ). Thus, all the studied species show a reduced leaf area and thick leaves (Table ), resulting in high LMA values when compared with other oak species from temperate climates (Corcuera et al ., ; Esteso‐Martínez et al ., ). Furthermore, such convergence is common in the evergreen sclerophyllous vegetation typical for Mediterranean‐type climates.…”
Section: Discussionmentioning
confidence: 97%
“…Such morphological leaf traits have been interpreted as adaptations to withstand summer drought (Morrow & Mooney, ; Poole & Miller, ; Baldocchi & Xu, ; Galmés et al ., ), given that water is the main limiting resource for plant growth in Mediterranean‐type climates (Di Castri, ; Rhizopoulou & Mitrakos, ; Mediavilla & Escudero, , ; Corcuera et al ., ). Thus, all the studied species show a reduced leaf area and thick leaves (Table ), resulting in high LMA values when compared with other oak species from temperate climates (Corcuera et al ., ; Esteso‐Martínez et al ., ). Furthermore, such convergence is common in the evergreen sclerophyllous vegetation typical for Mediterranean‐type climates.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, these species are able to survive even in the most xeric areas of this territory (Martín-Albertos et al 1998). Stomatal closure occurs in these species at water potential close to -3 MPa (Mediavilla and Escudero 2003;Vilagrosa et al 2003), and leaf size and cuticular transpiration are lower than in other congener species from mesic habitats (Kerstiens 1996;Esteso-Martínez et al 2006b). However, these three species show a high resistance to drought-induced cavitation (Tyree and Cochard 1996;Vilagrosa et al 2003;Corcuera et al 2005) when compared with the resistance found in some Mediterranean deciduous oaks (Corcuera et al 2006;Esteso-Martínez et al 2006a) or temperate deciduous oaks (Tyree and Cochard 1996).…”
Section: Introductionmentioning
confidence: 83%
“…An increased LSC has been related to climate dryness, as implies a higher ability for supplying water to the transpiring leaves in dry atmospheres [113,114]. In spite of these benefits, the reduction in supported leaf area per shoot concomitant with a decrease in leaf size has negative consequences in terms of carbon gain through the effect on leaf area ratio (LAR) [115], a major driver of the relative growth rate (RGR) [116]. To clarify this question, we have compared total foliage area and LAR in oak species from Mediterranean and Temperate climates growing in a common garden.…”
Section: Leaf Size Reductionmentioning
confidence: 99%